HUBUNGAN ANTARA NOMOPHOBIA DENGAN KEPERCAYAAN DIRI - Shanty Sudarji (Psibernetika, 2017)
Technology such as smartphones is growing rapidly. Development of applications such as instant messengers, social networks even easier for everyone to communicate, the distance is not an obstacle now. In addition to ease of access, the smartphone can also give confidence to users, in addition to models of smartphones increasingly stylish, applications that can be installed therein can make smartphone users are always updated with the latest news. The psychological impact caused by the use of smartphones on individuals and society in general about changing behavior and habits before and after use. Nomophobia (no-mobile-phone-phobia) is a type of phobia characterized by excessive fear if someone loses or does not exist near his smartphone. People who experience nomophobia always live in fear and are always anxious to put or keep his smartphone, so always take it anywhere to go. The questionnaire used to nomophobia is an adaptation of the questionnaire Yildirim (2014), composed of 4 dimensions with 20 statements. As for the questionnaire confidence, based on the theory of Justice (2002) derived into 3 dimensions with 46 statements. Results of the reliability values obtained for instruments confidence of 0.944, while the result of the reliability values for nomophobia instrument amounted to 0,939. The results of the data analysis of the correlation between nomophobia and confidence showed a p-value = 0.626> α = 0.05. This shows that there is no relationship between nomophobia with confidence. Keywords: Smartphone, Nomophobia, Confidence